LA ORIENTACIÒN DE LA GESTIÒN DEL TALENTO HUMANO COMO ROL PROTAGÓNICO EN EL DESARROLLO EDUCATIVO DE LA UNIDAD EDUCATIVA PADRE “MARCOS BENETAZZO” DE LA CIUDAD DE BABAHOYO, PROVINCIA DE LOS RIOS. - Morejón Yánez, Luis (2014)
In relation to education, it cannot be less to think that it will be impossible to change, if we don't have clear the type of teachers we need form to improve the learning and development of children and young people. Even when teachers are axes which constitute a very important social phenomenon that transformed the social, cultural and psychological thinking of youth, also recognizes the impact on education and its potentialities. In society is a clear lag in access of fairness but also in education. Apparently, today, should be taken actions at all levels (political, educational, economic), so that our youth is always a factor that it perpetuated social and educational inclusion where our children and young people are the most important. With safety education opens up many possibilities, but it also raises new demands. One of the most important challenges concerning the teaching task. The new demands on the teaching profession claim that they are flexible, tolerant as the main focus in education, in harmony with fellow and above all with influence of good values in the educational community, where parents also receive the information from the attention of teachers are responsible for developing their students thinking skills with reflection and criticality of the domain of a diversity of competencies required in the context of the knowledge society. Despite the curricular reforms of the last decade about the values of good living, they still exist in the educational system loss of values.